Platelets-rich-plasma in management of non operative post cruciate ligament injury - Giuseppe Messina; Pietro Cataldo; Francesco Mantia; Eleonora Maria Iovane; Carlotta Mantia; Micol Terrasi; Angelo Iovane (PAGEPress Publications, 2023)
Posterior cruciate ligament (PCL) injury is a rare ligamentous knee injury which most commonly occurs due to direct trauma; it represents only 0.65% of knee injuries. On the basis of magnetic resonance imaging (MRI), PCL injury is divided into surgical and non-surgical. In the last few years we have witnessed an increasing interest in regenerative medicine. The use of innovative techniques allow the reduction of rehabilitation times in sports injuries. Platelet-Rich-Plasma (PRP) is a plasma-derived which stimulate the tissue repair. The objective of our work is to compare the rehabilitation times in PCL non-operative injuries treated with standard conservative treatment and PCL injuries treated with autologous PRP followed by rehabilitation program. We divided patients into two different groups: Group A formed by patients who underwent a standard conservative rehabilitation program and Group B which included patients treated by ultrasound guided PRP injection and following physiotherapy program. Both groups of patients resumed sports activities; however the rehabilitation times for patients which had undergone treatment with autologous PRP injection were reduced compared to patients who underwent a standard conservative treatment.